2013
DOI: 10.1016/s1470-2045(13)70322-x
|View full text |Cite
|
Sign up to set email alerts
|

Fulvestrant plus anastrozole or placebo versus exemestane alone after progression on non-steroidal aromatase inhibitors in postmenopausal patients with hormone-receptor-positive locally advanced or metastatic breast cancer (SoFEA): a composite, multicentre, phase 3 randomised trial

Abstract: After loss of response to NSAIs in postmenopausal women with hormone-receptor-positive advanced breast cancer, maximum double endocrine treatment with 250 mg fulvestrant combined with oestrogen deprivation is no better than either fulvestrant alone or exemestane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
148
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(156 citation statements)
references
References 17 publications
2
148
0
3
Order By: Relevance
“…In particular, in patients with hormone-sensitive tumors, endocrine therapy can provide survivals similar to those obtained with chemotherapy (although with fewer objective responses) and has to be considered as a first choice in the absence clinical evidence of aggressive disease (4)(5)(6)(7)(8). Nevertheless, prolonged exposure to endocrine therapy may result in acquired resistance and subsequent progression of disease.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, in patients with hormone-sensitive tumors, endocrine therapy can provide survivals similar to those obtained with chemotherapy (although with fewer objective responses) and has to be considered as a first choice in the absence clinical evidence of aggressive disease (4)(5)(6)(7)(8). Nevertheless, prolonged exposure to endocrine therapy may result in acquired resistance and subsequent progression of disease.…”
Section: Introductionmentioning
confidence: 99%
“…At the lower dose, no benefit was seen when fulvestrant was compared with ais. Furthermore, the combination of fulvestrant (250 mg monthly) with anastrozole did not show any advantage compared with fulvestrant (250 mg monthly) or an ai alone as second-line treatment, as seen in the phase iii sofea trial described in Table ii 39 .…”
Section: Fulvestrant As a Single Agent Or In Combination Withmentioning
confidence: 90%
“…Combined analysis (Robertson et al 2003) indicated non-inferiority of fulvestrant in terms of the primary endpoint of time to progression (TTP). The SoFEA study compared fulvestrant (with or without anastrozole) with the steroidal AI 23:8 exemestane in patients with HR+ MBC and evidence of prior endocrine sensitivity in either the adjuvant or advanced setting (Johnston et al 2013). No difference in the primary endpoint of progression-free survival (PFS) was seen between the three arms.…”
Section: Fulvestrant Clinical Studiesmentioning
confidence: 99%